1998
DOI: 10.1002/(sici)1096-9136(199805)15:5<375::aid-dia585>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic peptide in Type 2 diabetes mellitus: response to a physiological mixed meal and relationship to renal function

Abstract: Relatively few data exist on atrial natriuretic peptide (ANP) characteristics in Type 2 diabetes mellitus (DM). Therefore, plasma immunoreactive ANP concentrations were measured before and for 4 h following the ingestion of a physiological mixed meal in 8 newly diagnosed, normotensive, normoalbuminuric, patients with Type 2 DM and 6 normotensive, non-diabetic controls. In patients with Type 2 DM, basal plasma ANP concentrations were 4.0 +/- 2.0 and not significantly changed following ingestion of the meal, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…Although some studies have demonstrated that plasma levels of ANP are normal in patients with type-2 diabetes [24], plasma concentrations of ANP have been shown to be elevated in the subgroup of patients with type-2 diabetes and microalbuminuria [25]. Our data would support the hypothesis that the elevated plasma ANP concentrations typically seen in patients with type-2 diabetes and hypertension, chronic hyperglycaemia and cardiac failure, may contribute to the development of microalbuminuria.…”
Section: Discussionsupporting
confidence: 77%
“…Although some studies have demonstrated that plasma levels of ANP are normal in patients with type-2 diabetes [24], plasma concentrations of ANP have been shown to be elevated in the subgroup of patients with type-2 diabetes and microalbuminuria [25]. Our data would support the hypothesis that the elevated plasma ANP concentrations typically seen in patients with type-2 diabetes and hypertension, chronic hyperglycaemia and cardiac failure, may contribute to the development of microalbuminuria.…”
Section: Discussionsupporting
confidence: 77%
“…6,21,22 Nonetheless, few studies have examined the relations of natriuretic peptide levels to other metabolic risk factors. 7,8 In smaller studies, inconsistent associations have been noted between plasma natriuretic peptides and glycemic status 9,23,24 or plasma lipids. 8 Olsen and colleagues 7 reported results of the only other large-scale investigation of plasma natriuretic peptide levels and metabolic risk factors.…”
Section: Comparison With Prior Studiesmentioning
confidence: 99%
“…Hypertension seems to elevate circulating natriuretic peptide levels, 7,8 whereas the effect of diabetes is less clear. 9,10 The availability of routine plasma natriuretic peptide measurements on more than 3000 individuals in the Framingham Heart Study made it possible to investigate the impact of obesity on natriuretic peptide levels and to distinguish this impact from that of hypertension, diabetes, and other characteristics.…”
mentioning
confidence: 99%